2015
DOI: 10.1091/mbc.e15-05-0284
|View full text |Cite
|
Sign up to set email alerts
|

The α-arrestin ARRDC3 mediates ALIX ubiquitination and G protein–coupled receptor lysosomal sorting

Abstract: The novel ALIX-dependent GPCR sorting pathway is regulated by the a-arrestin ARRDC3. A critical role is also shown for the E3 ubiquitin ligase WWP2 in regulation of ALIX ubiquitination and lysosomal sorting of GPCRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 38 publications
5
90
1
Order By: Relevance
“…1D). Although our studies suggest that ARRDC3 is primarily localized at EEA1-positive early endosomes in HEK293 and BT549 cells, it's worth noting that Dores et al (35) found that overexpressed ARRDC3 was equally distributed on both early and late endosomes in HeLa cells. Thus, it appears that the cellular localization of ARRDC3 is dependent on both the cell type and expression level.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…1D). Although our studies suggest that ARRDC3 is primarily localized at EEA1-positive early endosomes in HEK293 and BT549 cells, it's worth noting that Dores et al (35) found that overexpressed ARRDC3 was equally distributed on both early and late endosomes in HeLa cells. Thus, it appears that the cellular localization of ARRDC3 is dependent on both the cell type and expression level.…”
Section: Discussioncontrasting
confidence: 64%
“…Although previous studies suggested that ARRDC3 localizes to both the plasma membrane and endocytic vesicles, these observations were made in heterologous cell lines overexpressing ARRDC3 (15,19,34,35). Using fixed-cell confocal immunofluorescence microscopy, we demonstrated that both overexpressed (Fig.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Upon PAR1 activation, ARRDC3 recruits HECT-type E3 ubiquitin ligase WWP2 which ubiquitinates ALIX. In this way, ARRDC3 facilitates the sorting of PAR1 into ILVs of MVBs [110]. The mechanisms that control ALIX-dependent GPCR sorting at the multivesicular endosomes remain poorly understood; however, it is speculated that ubiquitin may regulate ALIX by facilitating its dimerization, which in turn can promote its interaction with the ESCRT-III complex [110].…”
Section: Lysosomal Degradationmentioning
confidence: 99%